1994
DOI: 10.1073/pnas.91.26.12902
|View full text |Cite
|
Sign up to set email alerts
|

In vivo occupancy of the vitamin D responsive element in the osteocalcin gene supports vitamin D-dependent transcriptional upregulation in intact cells.

Abstract: The steroid hormone vitamin D is a principal mediator of skeletal homeostasis. 1,25-Dihydroxyvitamin D3 treatment of ROS 17/2.8 osteoblast-like cells results in a ligand-dependent increase in transcription of the bone-specific osteocalcin gene. This transcriptional upregulation requires the positive cis-acting vitamin D responsive element (VDRE). We have used the ligation-mediated polymerase chain reaction to demonstrate that protein occupancy of the VDRE within the intact cell correlates with increased synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…Truss et al (1994), by studying occupancy of the PR remains in vivo, showed that antiprogestins inhibit PR occupancy in the MMTV promoter in vivo, even though antagonist-bound PR was capable of binding to the PRE in vitro. A ligand induced change in VDRE occupancy in vivo has also been noted (Breen et al 1994).…”
Section: Discussionmentioning
confidence: 90%
“…Truss et al (1994), by studying occupancy of the PR remains in vivo, showed that antiprogestins inhibit PR occupancy in the MMTV promoter in vivo, even though antagonist-bound PR was capable of binding to the PRE in vitro. A ligand induced change in VDRE occupancy in vivo has also been noted (Breen et al 1994).…”
Section: Discussionmentioning
confidence: 90%
“…However, unlike the rat osteocalcin gene, where liganded VDR has been shown to associate with the positive VDRE via in vivo footprinting, (160) no evidence has been provided that VDR directly binds to the IL-2 promoter in a ligand-dependent fashion, in vivo.…”
Section: Vdr (Rxr?) Rxr (Vdr?)mentioning
confidence: 99%
“…Among the primary VD responsive genes, i.e. genes carrying a functional VDRE, we have studied the expression of the hOC (Breen et al, 1994) and the p21 waf-1 gene (Liu et al, 1996). Among the early responsive gene associated with the monocytic differentiation program we have studied the expression of CD14 (Zhang et al, 1994) and HMSE-1 (Uphoff et al, 1993).…”
Section: Ability Of Endogenous Vdr To Activate Transcription Of Vdre-mentioning
confidence: 99%